A Tax Compliance Model with Legal Certainty Factors: A Laboratory Experiment Study - Paramita Anjelina, Rahayu; Suwandi, Suwandi (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: Tax compliance is critical for the effective functioning of government and is influenced by various factors, including legal certainty and enforcement. Specific Background: Previous studies have explored tax compliance in relation to law enforcement, emphasizing the role of sanctions and audits. However, inconsistencies in findings regarding the impact of law enforcement on compliance highlight a need for further investigation. Knowledge Gap: Limited research has employed a quantitative laboratory experimental approach to examine the influence of law enforcement intensity on tax compliance. Aims: This study aims to investigate the effect of high versus low law enforcement on taxpayer compliance using a 2x1 factorial experimental design. Results: The results indicate a significant difference in compliance levels between high and low law enforcement conditions, with higher enforcement leading to greater compliance. Novelty: This study introduces a laboratory experimental method to assess tax compliance, providing a more controlled environment to observe the impact of enforcement intensity. Implications: The findings suggest that increasing the severity of law enforcement may enhance tax compliance, offering insights for policymakers to design more effective compliance strategies and to reconsider the reliance on programs such as tax amnesty, which might undermine compliance in the long term.